PENGARUH AKTIVITAS MEMBATIK ECO PRINTING TERHADAP MOTORIK HALUS PADA SISWA TUNADAKSA DI SLB NEGERI 1 BANTUL - Solikhah, Maratun; Hidayat, Luqman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the effect of eco-printing batik activities on the fine motor skills of students with physical disabilities (students with orthopedic impairments) at a Special School (SLB). The study employed a quantitative approach using a pre-experimental method with a One-Group Pretest–Posttest Design. The research subjects consisted of five students with physical disabilities, selected using a total sampling technique. Data were collected through observation using a validated fine motor skills assessment instrument. The assessment covered several aspects, including hand-eye coordination, finger strength and flexibility, manipulative skills, concentration and accuracy, sensorimotor stimulation, independence, motivation and self-confidence, and participation in educational therapeutic activities. The data were analyzed using descriptive statistics and the Wilcoxon Signed-Rank Test. The results showed that the mean pre-test score was 56.60, which increased to 94.60 on the post-test. The Wilcoxon Signed-Rank Test yielded an Asymp. Sig. (2-tailed) value of 0.042 (p < 0.05), indicating a statistically significant difference between the pre-test and post-test scores. Therefore, it can be concluded that eco-printing batik activities have a significant positive effect on improving the fine motor skills of students with physical disabilities at a Special School (SLB). These activities can be considered an effective alternative instructional approach for enhancing students' fine motor development through meaningful, hands-on learning experiences.